南極宗谷海岸の丸湾大池の完新世における古陸水学的研究 - 伊東, 敬祐; 谷, 幸則; 瀬戸, 浩二; 渡邊, 隆広; 大谷, 修司; 伊村, 智; 中村, 俊夫; 本多, 英介; 井上, 源喜; Keisuke, Ito; Yukinori, Tani; Koji, Seto; et al. (2013)
第4回極域科学シンポジウム 個別セッション：[OB] 生物圏 11月13日（水）13:00-14:15 国立国語研究所 ２階ラウンジ conference object